An Active Metamaterial for Polarization Manipulating. Issue 10 (14th July 2014) - Ma, Xiaoliang; Pan, Wenbo; Huang, Cheng; Pu, Mingbo; Wang, Yanqin; Zhao, Bo; Cui, Jianhua; Wang, Changtao; Luo, Xiangang
<x xml:space="preserve">Abstract</x> An active metamaterial is proposed based on the concept of chiral structure, which switches its chirality by controlling the working states of the PIN diodes in its unit cells. This metamaterial has the function of manipulating the incident linearly polarized wave into a right‐handed circularly polarized or left‐handed circularly polarized one. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>